Questões em torno da transferência de custódia de documentos entre arquivos públicos - Troitiño, Sonia [UNESP] (My University, 2012)
This paper discusses the different forms and conditions of incorporating collections from the judiciary by executive bodies. For such, we use the custodial history of the Juízo de Órfãos de São Paulo archives as a reference. An instance of the Brazilian justice between the 16th and 20th centuries, the Juízo de Órfãos de São Paulo is currently fragmented in several institutions of custody and under different denominations. Similarly, other archives from judiciary bodies underwent similar processes for custody transfer. However, this type of situation is not restricted to the past: nowadays, even under legally established norms and guidelines for the implementation of document management programs, it is still possible to find, recurrently, the adoption of similar procedures for the incorporation of collections. We therefore intend to establish a parallel between these two moments and the Brazilian archival legislation in force.
Issues around the transfer of records custody among public archives
Keywords: Court archives; Custodial history; Juízo de órfaos de sao paulo; Records transfer